Desain Interior Ruang Baca Perpustakaan IAIS Sambas untuk Kenyamanan Perspektif Pustakawan - Azwar Azwar (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Reading room has an important role in the library. In the reading room, users spend a long time to fulfill their information needs. Every user who comes to the library will feel at home in the library if the room is adequate and has a comfortable atmosphere. Interior design in this case is very important to consider and get great attention by librarians. The Sambas iais library occupies a temporary building that is used for its current operations. This building is conceptualized as comfortable as possible by the librarian to provide services to the public. The library reading room is placed together with the collection room without any dividers or barriers. Placement like this is done for the efficiency of the room. This research uses qualitative methodology with a phenomenological approach. This research concludes that the interior design of the library is conceptualized by adjusting the room area of the building facilities and the available funds. Library furniture is dominated by wood material with brown color. For the balance of room temperature in the library using air conditioning, fans and windows.